Metastatic Spread of Osteosarcoma - Price, C. H. G. (Nature Publishing Group, 1973)
A study is presented of the rate of metastatic spread of osteosarcoma. The series consists of 123 tumours in long bones and 26 elsewhere in the skeleton. All tumours occurred in otherwise normal bones and were histologically proven. With a few stated exceptions all the cases were consecutively registered. Both the mean disease-free interval from the time of starting treatment and the crude survival curves are given. The long bone cases are analysed by groups according to the method of treatment, the patient's sex, age and tumour site. There were too few tumours of all other sites to warrant this discriminative treatment. Whilst the results of surgical treatment are better than for radiotherapy or a combined technique, the differences are not statistically significant and the information is recorded primarily to assist the evaluation of new forms of treatment of occult and overt metastases. Some problems in connection with such clinical trials are discussed briefly.